Viscoelastic melt rheology and time-temperature superposition of polycarbonate – multi-walled carbon nanotube nanocomposites - Choong, Gabriel Y.H.; De Focatiis, Davide S.A.; Hassell, David G. (Springer, 2013)
This work investigates the linear and non-linear viscoelastic melt rheology of four grades of polycarbonate melt-compounded with 3 wt% Nanocyl NC7000 multi-walled carbon nanotubes and of the matching matrix polymers. Amplitude sweeps reveal an earlier onset of non-linearity and a strain overshoot in the nanocomposites. Mastercurves are constructed from isothermal frequency sweeps using vertical and horizontal shifting. Although all nanocomposites exhibit a second plateau at ~105 Pa, the relaxation times estimated from the peak in loss tangent are not statistically different from those of pure melts estimated from cross-over frequencies: all relaxation times scale with molar mass in the same way, evidence that relaxation of the polymer network is the dominant mechanism in both filled and unfilled materials. Non-linear rheology is also measured in large amplitude oscillatory shear. A comparison of the responses from frequency and amplitude sweep experiments reveals the importance of strain and temperature history on the response of such nanocomposites.